2016
DOI: 10.1111/fwb.12828
|View full text |Cite
|
Sign up to set email alerts
|

Ciliate community structure and interactions within the planktonic food web in two alpine lakes of contrasting transparency

Abstract: Summary Climate warming is accelerating the retreat of glaciers and recently, many ‘new’ glacial turbid lakes have been created. In the course of time, the loss of the hydrological connectivity to a glacier causes, however, changes in their water turbidity and turns these ecosystems into clear ones.To understand potential differences in the food‐web structure between glacier‐fed turbid and clear alpine lakes, we sampled ciliates, phyto‐, bacterio‐ and zooplankton in one clear and one glacial turbid alpine lake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 68 publications
(99 reference statements)
5
35
0
Order By: Relevance
“…Recently, we showed that some planktonic ciliate species are quite abundant in both clear and turbid alpine lakes, while other mainly particle‐associated species are only present in turbid habitats (Kammerlander et al. ). Here, we found Paramecium cf.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, we showed that some planktonic ciliate species are quite abundant in both clear and turbid alpine lakes, while other mainly particle‐associated species are only present in turbid habitats (Kammerlander et al. ). Here, we found Paramecium cf.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to highly turbid lakes, in clear alpine lakes UVR (280–400 nm) can penetrate the entire water column (Kammerlander et al. ; Sommaruga and Psenner ). The response to UVR of aquatic organisms originating from alpine lakes of contrasting UVR transparency was recently compared in copepods using a single‐cell gel electrophoresis method (comet assay; Tartarotti et al.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In one clear alpine lake, Kammerlander et al (2016) identified the underwater solar UVR as the primary factor influencing the distribution pattern of the dominant ciliates prior to food resources (phytoplankton). UVR experiments conducted with ciliates identified species-specific effects resulting in, for example, DNA-damage, abnormal swimming behavior, retarded growth rates, or cell death (e.g., Giese 1945, Martini et al 1997, Sanders et al 2005, Summerer et al 2009).…”
Section: Introductionmentioning
confidence: 99%